Perubahan Ekonomi dan Perkembangan Peradaban Islam di Palembang Abad XVII – XIX M: Telaah atas Naskahnaskah Kontrak Sultan Palembang - Endang Rochmiatun (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2015)
Artikel ini berbicara tentang hubungan antara perubahan dan perkembangan ekonomi selama Kesultanan Palembang, terutama di era Sultan Mahmud Badaruddin I (1724-1757). Tujuan dari artikel ini adalah untuk menjawab pertanyaan: apa sektor ekonomi yang memberikan manfaat bagi Sultan, sehingga ia mampu memperluas peradaban? Bagaimana strategi Sultan Palembang dalam memajukan ekonomi yang mampu memengaruhi perkembangan peradaban Islam di Palembang. Temuan dari penelitian ini menunjukkan bahwa “lada” merupakan komoditas penting sebagai sumber pendapatan utama kesultanan. Sumber pendapatan lain datang dari “timah” yang berasal dari wilayah koloni yang bernama Bangka. Sultan Palembang melakukan dua bisnis yang saling bertentangan pada waktu yang sama: melakukan bisnis yang legal dengan pelindungnya VOC, dan di sisi lain, ia juga melakukan perdagangan timah di pasar gelap. Selanjutnya, ia juga menjual barang-barang lain yang benar-benar dilarang oleh VOC untuk membiayai penambangan timah. Keuntungan dari perdagangan ini mampu membawa kemakmuran Kesultanan Palembang dan kemajuan peradaban. Misalnya, Sultan mampu membangun kendaraan dan beberapa lembaga Islam.Kata Kunci: Palembang Sultanate, Sultan Mahmud Badaruddin, VOC, timah, lada This paper concerns on the relationship between the changing and development of economy during the Palembang’s Sultanate, especially in the era of Sultan Mahmud Badaruddin I (1724-1757) and the development of Islamic civilization. The objectives of this essay are to answer these questions; what economic sectors are that give benefits to the Sultan, so that he was able to expand the civilization? How are the Sultan of Palembang’s strategies to make economic advancement which affected to the development of Islamic civilization in Palembang. Finding of this research shows that the “pepper” from the headwaters area was an important commodity that played as the main source of income for sultanate. Another primary source of revenue came from “tin” which was from its colony named Bangka. Sultan of Palembang operated two contradict businesses at the same time; the first, he did a legal business with his protector namely VOC. On the other hand, he also traded tin in the black market in order to gain the redemption benefits. Furthermore, he also sold other goods which were actually prohibited by VOC, this aimed to finance the tin mining. The profits of trading on tin brought prosperity to Palembang Sultanate and advancement in civilization, for instance Sultan build vehicle and several Islamic institutions.Keywords: Palembang Sultanate, Sultan Mahmud Badaruddin, VOC, pepper, tin